(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: Describe the infection situation and characteristics of bacteria isolated on preserved skull bone tissue. Subjects and methods: Descriptive, retrospective study of 1162 skull bone tissue samples randomly selected from tissues preserved at the tissue bank of Viet Duc University Hospital. Results: 1162 patients including 898 men (77.28%), 264 women (22.72%); 1067 cases (91.82%) had craniotomy due to traumatic brain injury. The infection rate before radiation was 4.56%; after radiation was 0.17%. Common bacterial strains were Staphylococcus aureus (15.52%), Staphylococcus epidermidis (15.52%) and Pseudomonas aeruginosa (13.79%). Bone fragments with multiple fascia, hematoma, and crushed fractures had an infection rate of 7.65%, higher than the group with clean bone fragments of 4.38%. The infection rate according to the transportation time within the day (≤ 24 hours) was 1.88%; from 1-2 days was 4.72%, from 3-7 days was 7.65%, and over 7 days was 6.52%. Samples from external hospitals had a contamination rate of 9.38%, significantly higher than that of internal hospital samples (0.48%) (p < 0.01). Conclusion: The infection rate before irradiation was 4.56%, which decreased to 0.17% post-irradiation. S.aureus, S.epidermidis, and P.aeruginosa are common bacterial strains. The process of collecting, processing, and preserving skull bone tissue has many factors that contribute to the increased risk of infection.